Monitoring periodontal lesions and their effects during pregnancy: microbiological aspects of the oral cavity and amniotic fluid in pregnant ewes - Souza, Natália C. [UNESP]; Ramos, Thamiris N.M. [UNESP]; Borsanelli, Ana Carolina; Saraiva, Júlia R. [UNESP]; Ferreira, Evandro M.; Schweitzer, Christiane M. [UNESP]; Elerson, Gaetti-Jardim [UNESP]; Dutra, Iveraldo S. [UNESP] (FapUNIFESP (SciELO), 2023)
Periodontitis affects the teeth supporting tissues, leading to tooth loss and damage to animal health. Evidence in humans suggests that oral microorganisms spread systemically, increasing the risk of pregnancy disorders such as miscarriage, prematurity, and low birth weight. This study aimed to verify whether periodontopathogenic microorganisms reach the transplacental unit, culminating in problems in pregnant ewes. After analyzing the oral cavity, 10 clinically healthy pregnant ewes (OGCH group) and 10 pregnant ewes with periodontitis (OGP group) were selected. The subgingival biofilm was collected for the polymerase chain reaction (PCR) test and amniotic fluid for both the PCR and interleukin (IL) analysis. Peripheral blood was collected for complete blood count, and analyses of IL-6, IL1-β, and tumor necrosis factor-α were performed. Placental fragments were collected to assess the inflammatory changes using optical microscopy. After giving birth, both the ewes and their lambs were weighed. On clinical examination, a positive correlation between bleeding and suppuration (correlation index – CI=0.54), suppuration and marginal gingivitis (CI=0.34), and marginal gingivitis and edema (CI=0.54) was observed. The weights of the ewes (p=0.013) and their respective lambs (p=0.04) in the OGP group were lower than those of their OGCH group counterparts. The hematological analysis revealed that the OGP group ewes showed a slight increase in the mean corpuscular volume (p=0.2447), segmented cells (p=0.3375), and eosinophils (p=0.3823) when compared with the OGCH group ewes, without a statistical difference. Regarding the microorganisms detected in the oral cavity, there was a significant difference between the occurrence of periodontal pockets and the presence of Fusobacterium necrophorum (p=0.0328), Porphyromonas asaccharolytica (p=0.0392), and the Mollicutes class (p=0.0352). Staphylococcus genus (p=0.9107) and Archaea domain (p=0.7245) were detected in the amniotic samples of both groups, without a significant difference, whereas P. asaccharolytica (p=0.2685) was only detected in one sample in the OGCH group. The expression of cytokine IL-6 in the OGP group differed significantly between the prepartum and postpartum periods (p=0.0039); moreover, it differed significantly in the postpartum period between the OGCH and OGP groups (p=0.0198). Histological examination showed a higher percentage of placental changes in the OGP group (70%) than in the OGCH group, such as the presence of macrophages, neutrophils, plasma cells, and multifocal areas of calcification. These results do not corroborate the hypothesis of dissemination of oral microorganisms to the placental unit, suggesting that it constitutes placental isolation in sheep.
Keywords: amniotic fluid; ewes; gestational complications; oral cavity; Periodontitis; premature lambs; sheep